Effect of Moisture Content on California Bearing Ratio of Subgrade at a Road Settlement Area - Fitriana; Heni Pujiastuti; Ahmad Zarkasi (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Road subgrade performance is strongly influenced by moisture conditions because changes in water content can alter soil density, strength, and bearing capacity. This study investigated the effect of moisture conditions on the California Bearing Ratio (CBR) of subgrade soil collected from a road settlement area in Dopang Village, Gunungsari District, West Lombok Regency, Indonesia. A laboratory experimental method was employed, including natural moisture content, specific gravity, particle-size distribution, Atterberg limits, Standard Proctor compaction, and CBR testing under unsoaked and 96-hour soaked conditions. The soil had a natural moisture content of 38.90%, specific gravity of 2.70, 26.30% material passing the No. 200 sieve, liquid limit of 31.41%, plastic limit of 21.81%, and plasticity index of 9.60%. The Standard Proctor test produced an optimum moisture content of 18.33% and a maximum dry density of 1.365 g/cm³. The CBR value decreased from 8.142% in the unsoaked condition to 3.392% after soaking, representing a reduction of approximately 58.3%. The results demonstrate that water saturation substantially reduces subgrade bearing capacity. The findings indicate that moisture control, adequate drainage, and appropriate subgrade improvement are essential for reducing the risk of recurrent road settlement at the study location.